2016
DOI: 10.1007/s13127-016-0268-4
|View full text |Cite
|
Sign up to set email alerts
|

Update of genetic information for the white-clawed crayfish in Spain, with new insights into its population genetics and origin

Abstract: The white-clawed crayfish is endemic to western and southern Europe and its populations have decreased over recent decades. Spanish populations are generally poorly represented in scientific reports and are usually studied only with a single molecular marker. Here, we use two mitochondrial markers (cytochrome oxidase subunit I and rDNA 16S genes) to examine levels and patterns of genetic structure across the range of the species' distribution in Spain. Data reveal the existence of two main genetic groups of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 73 publications
(91 reference statements)
6
20
0
Order By: Relevance
“…For the last few years, the genetic variability of Spanish white-clawed crayfish has been assessed with mitochondrial and nuclear markers by sampling a significant number of populations throughout its distribution range in the country (Beroiz et al, 2008;Matallanas et al, 2013Matallanas et al, , 2016PedrazaLara et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For the last few years, the genetic variability of Spanish white-clawed crayfish has been assessed with mitochondrial and nuclear markers by sampling a significant number of populations throughout its distribution range in the country (Beroiz et al, 2008;Matallanas et al, 2013Matallanas et al, , 2016PedrazaLara et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…
11recently published (Matallanas et al, 2016). Our work had concluded that the knowledge 12 generated by disparate scientific disciplines robustly converged to indicate that
13

Austropotamobius italicus is non-native species in Spain, but Matallanas et al (2016)

16

First, we point out that the mono-disciplinary approach followed by Matallanas et al (2016) is 17 much weaker than the transdisciplinary approach used and advocated by Clavero et al (2016).

18

Second, we believe that the genetic patterns presented by Matallanas et al (2016)

…”
mentioning
confidence: 85%
“…First, we point out that the mono-disciplinary approach followed by Matallanas et al (2016) is 17 much weaker than the transdisciplinary approach used and advocated by Clavero et al (2016).…”
mentioning
confidence: 92%
“…Later genetic studies have shown that A. astacus has inhabited Swedish aquatic ecosystems since the last ice age, thus being native to Sweden (Edsman et al, 2002;Gross et al, 2013;Dannewitz et al, 2021). Similarly, A. pallipes has been claimed to have been introduced to Spain from Italy only in the 1500s (Clavero et al, 2016), despite genetic evidence dating the species origin on the Iberian Peninsula from the last glaciation (Matallanas et al, 2011(Matallanas et al, , 2016Jelić et al, 2016;Martín-Torrijos et al, 2021a). Such scenarios, of course, create confusion and employ everyone to waste resources in order to correct the deliberate misinterpretation in any given case.…”
Section: Twisting the Definitions And Creating New Language To Cause Confusionmentioning
confidence: 99%